Wacana, Satu Alternatif Memahami Islam - Prasetyo, Hendro (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
This book aim to describe the features of local forms of Islam in the Gayo highland, central part of the Aceh province, Sumatra. Gayo people have been Muslim since at least the seventeenth century, by which time they were incorporated into the Acehnese kingdom. Their religious mode represent the somewhat distinctive character of Islam generally found in this country. They have developed their local knowledge by elaborating, transforming and adapting elements from broader Muslim traditions. They describe the existence of spiritual beings and the power of language by using the Muslim idea of stainhood. They explain the power of spells and the ability to hunt and farm through Muslim narrative about Adam.DOI: 10.15408/sdi.v1i3.854